Pengaruh Net Profit Margin,Price To Book Value Terhadap Return Saham Syariah Dengan Inflasi Sebagai Variabel Moderasi - Rani Ariska Pratiwi; Elyanti Rosmanidar; Ferri Saputra Tanjung (STEKOM PRESS, 2024)
Mining companies are one of the companies that have great prospects in the future. Mining companies are one of the corporate sectors that are targeted for investment, this causes investors to often calculate share returns for their investments in companies in this sector. Stock returns in companies tend to fluctuate or experience erratic increases and decreases in stock returns. The increase or decrease in stock returns is caused by internal and external factors, internal factors can be seen through financial reports and external factors can be seen from macroeconomic and other factors. This research is secondary data, namely it comes from financial reports of mining companies registered in JII70 for the 2018-2022 period. This research is included in the type of quantitative research, using Eviews as a statistical medium and the statistical methods used in this research are multiple linear regression analysis, panel data testing, classical assumption testing, and hypothesis testing. while the results of this research show that partially both Net Profit Margin and Price To Book Value have a positive and significant effect on Stock Returns as well as simultaneously Net Profit Margin and Price To Book Value together or simultaneously have a positive and significant effect on Stock Returns while inflation weaken the relationship Net Profit Margin and Price To Book Value on Share Returns in mining companies registered on JII70.